Policy Texts e o papel das ideias nas políticas públicas: Vis\~oes estatais sobre as mulheres no PPA 2016-2019 - Janine Mello; Ana Camila Ribeiro Pereira; Danusa Marques (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The article aims to contribute for the comprehension of how State visions on representations of women permeate the content of objectives, goals and initiatives presented on PPA (2016-2019) understood as a governmental planning instrument on which guidelines for public action are stablished for a certain period of time. In this sense, the general character and thematic diversity presents on PPA may allow the identification of more general compromises and guidelines and, a priori, capture representations of what constitutes the main governmental concerns of policies formulation and implementation related to women.
Keywords: H11; 330; women; public policies; State; policy texts; PPA; gender